Role of vitamin E and zinc sulfate in infertile men (Tikrit Journal of Pharmaceutical Sciences, 2023)
Infertility affects 15-30% of couples that are trying to conceive, about half of these cases, male partner is the sole contributing factor. Infertility remains a controversial problem worldwide, male infertility caused by different anatomical defect like obstruction of seminal tube and neurological abnormalities, resulting in abnormal spermatogenesis which weakens the function of sperm.Follow-up study done for 60 infertile men with age range between 30-45 years. Data collected was carried out during the period from April 2019 to August 2019 in Bajii city which include seminal fluid analysis, determination of testosterone, prolactin, and T3 and T4 before and after treatment with vitamin E(800 I.U/daily) and zinc sulfate(50mg/daily) which last for three months , all data were presented as mean and standard deviation. In this study we exclude any disease or abnormal condition that related to this group.There are 60 infertile men participated in this study, age range between 30-45 years. In these cases we measured the seminal fluid analysis, determination of testosterone, prolactin, and T3 and T4 before and after treatment with vitamin E(800 I.U/daily) and zinc sulfate(50mg/daily) which last for three monthsAbout the seminal fluid analysis, there is a significant increase in number of sperm in infertile men after the treatment, and also there is a significant increase in activity of sperm after treatment. Regarding the seminal fluid analysis, there is a significant increase in number of sperm in infertile men after the treatment compared with this before treatment and also there is a significant increase in activity of sperm after treatment compared with this before treatment. About the percentage of non-motile sperm, there is a significant decrease in this percentage after treatment compared with this before treatment, also there is decrease in percentage of abnormal sperm shape after treatment compared with this before treatment, while there is a significant increase in percentage of normal sperm shape after treatment compared with this before treatment About the concentration of prolactin, there is none significant difference between its level after treatment and before treatment. Regarding the concentration of testosterone, there is a significant elevation in its concentration after the treatment compared with its concentration before treatment and About the concentration of T3 and T4, there is none significant difference in its concentration after treatment and before treatment respectively.